The productivity and quality of seeds of winter triticale varieties with various seeding rates - T. A. Babaytseva; A. M. Lentochkin; I. A. Ryabova (Зерновое хозяйство России, 2018)
The seed quality is the most important factor for productivity increase of all agricultural crops. Its formation depends on many factors including agro technologies. It’s common knowledge that seed quality depends on a degree of plant density. But with the introduction of new varieties into production the problem of optimal seeding rates in seed-growing remains very important. The article gives the results of the research in 2013-2015, the purpose of which was to determine the best seeding rate giving the highest productivity and quality of seeds and increasing the coefficient of reproduction of winter triticale seeds ‘Izhevskaya 2’ and ‘Zimogor’ in the Middle Pre-Urals. For the purpose, Izhevsk SAA put a two-factor trial, where A was the varieties ‘Izhevskaya 2’ and ‘Zimogor’; the factor B was a seeding rate of germinated seeds of 3-8 mln per ha and the control was 6 mln per ha. The study was conducted according to the conventional methods. It has been determined that winter triticale ‘Izhevskaya 2’ with a seeding rate of 5 mln per ha and ‘Zimogor’ with a seeding rate of 6 mln per ha gave the increased yields and improved seed quality. With a rapid reproduction it’s possible to sow both varieties with the seeding rates of 3 and 4 mln per ha, as in comparison with the indexes of the control variant (a seeding rate of 6 mln per ha) the coefficient of reproduction of ‘Izhevskaya 2’ increases on 2.3-4.6 points, ‘Zimogor’ on 3.6-7.5 points; 1000-seed weight increases on 0.3-0.6g and 2.4-3.0g respectively; the seeds give better sprouts which can be valuated higher on 0.04-0.09 p and 0.13-0.31p respectively.